When Recognition Violates the Obligation of Non-Recognition: A Legal Criticism of the U.S. Proclamation of Recognition of the "Sovereignty" of Morocco over the Western Sahara - Hadj Cherif, Hamza (Technium Social Sciences Journal, 2021)
The purpose of this study is to examine the legality of the U.S. proclamation of recognition of Moroccan “sovereignty” over the territory of Western Sahara in light of the legal status of this territory and the evolution of contemporary international law, particularly with regard to the obligation of nonrecognition of a situation created by a serious violation of peremptory norms.